The constitutional and legal status of the Ukrainian people - ALIONKIN, Олексій; KOLODIY, Олексій (Ius Modernum, 2019)
Background. Awareness of its constitutional and legal status is an important element in the formation of the Ukrainian people as a self-dependent and independent, in the process of building Ukraine as a democratic and legal state. Analysis of recent researches and publications. This problem is studied by such scientists as: Punchyshyn A. V. and others. The aim of the article is to study the systematic and structural analysis of the constitutional and legal status of the Ukrainian people. Materials and methods. The information base of the research is the Constitution of Ukraine and the work of domestic and foreign scientists. The methodological basis of this scientific article is a number of philosophical, general scientific and special-scientific methods and principles. Results. As a result, a systematic and structural analysis of the constitutional and legal status of the Ukrainian people was investigated. The modern approaches to understanding the following legal phenomena: legal status, legal status of the state, constitutional and legal status of the people, elements of the legal status of peoples was considered. The concept, features, types and elements of the constitutional and legal status of the Ukrainian people are formulated. Conclusion. The constitutional and legal status of the Ukrainian people is a legal phenomenon that characterizes its place and role in the national society and the state, among other peoples, foreign societies and states, international unions.